Breeding bird communities in hills with chalk outcrops in national nature park “Dvorichanskyi” - Banik, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The breeding bird communities in hills with chalk outcrops were studied in national nature park ‘Dvorichanskyi’ (Kharkiv region, Eastern Ukraine) in 2010–2016 years. The birds were counted 1–2 times per year by total-area census method at 3 plots of unequal size (17.8, 33.2, and 41.0 ha). The total of 38 breeding species was recorded. The overall mean density was 236.7 pairs/km2. The dominants were Red-backed Shrike (Lanius collurio) (mean density – 38.8 pairs/km2; relative abundance – 16.8%), Eurasian Skylark (Alauda arvensis) (33.5; 14.3), and Yellowhammer (Emberiza citrinella) (29.3; 12.6). Greater Whitethroat (Sylvia communis) (20.3; 7.7), Whinchat (Saxicola rubetra) (17.4; 7.1) and Barred Warbler (Sylvia nisoria) (16.7; 6.9) co-dominated. Tawny Pipit (Anthus campestris) (10.4; 4.6), Tree Pipit (A. trivialis) (10.4; 4.6), Common Stonechat (Saxicola torquata) (5.3; 2.2), Northern Wheatear (Oenanthe oenanthe) (7.7; 3.2), and European Greenfinch (Chloris chloris) (6.9; 3.0) are less numerous but occurred regularly. Shrubland & woodland species form a core of the breeding bird communities in hills with chalk outcrops. This group contributed much more than others to the overall species richness (61%) and overall abundance (62%).